Best Practice of Financial Management in SMEs Operation in Digital times - Nenden Hendayani; Muzakir Muzakir; Yuliana Yuliana; Muhammad Asir; Abdul Wahab (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
All activities will result in better outcomes with good practice, similar to business. The motivation behind this business writing study was for an inside and out comprehension of the best practice of MSME financial administration in the current advanced time. To address this problem inquiry, we began writing a data set of worldwide distributions talking about issues from a financial administration point of view in SMEs and all-tech circles. We need to foster a pursuit and study information beginning with coding data for deciphering information in making ends that approach primary responses and understandings. We look for information on this web-based web data set on applications distributed somewhere in the range of 2010 and 2021, where we plan it as a subjective expressive review with a framework information search based on conditions connected with best strategic approaches like financial information for SMEs tasks and seasons of the contest in the computerized time. Along these lines, this information manages auxiliary information from prior or optional information from the proof of studies that have been done already. Accordingly, best practices include single service, prioritizing customers, and prioritizing customer data, courteous billing, using the best application, keep good records.